The Medical Cannabis Dilemma in Indonesia From an Islamic Law Perspective: Between Benefit and Harm - Rahmad Setyawan; Hayatul Islami; Doli Witro; Ahmad Mundzir; Muhammad Asyrofudin (Institut Agama Islam Negeri Curup, 2026)
The prohibition of cannabis under Indonesian narcotics law has generated continuing debate regarding its potential use for medical treatment. This study aims to examine the legal status of medical cannabis from the perspective of Islamic law and to formulate a governance framework for its limited medical use in Indonesia. This research employs a qualitative normative legal method through statutory, conceptual, and case approaches, supported by literature review and semi-structured interviews with Islamic scholars, legal academics, and healthcare professionals. The findings reveal that Islamic law does not treat medical cannabis through an absolute prohibition paradigm but through a contextual assessment of maṣlaḥah and mafsadah. Medical cannabis may be permitted in exceptional circumstances when there is an urgent therapeutic need, scientific evidence of efficacy, no equally effective alternative treatment, and strict medical and governmental supervision. The study further identifies six Islamic bioethical principles relevant to the regulation of medical cannabis, namely protection of life, protection of intellect, public benefit, necessity, harm reduction, and the right to health. Based on these principles, the study proposes a maqāṣid al-sharī‘ah-based governance model emphasizing scientific validation, specialist supervision, patient registration, pharmaceutical control, stakeholder involvement, and periodic risk assessment. The study concludes that a limited and highly regulated medical cannabis policy is compatible with the objectives of Islamic law and may serve as a basis for future reform of Indonesian narcotics regulation.